Mempersiapkan Guru Ppkn yang Profesional di Masa Depan dalam Menciptakan Keterampilan dan Kompetensi yang Dibutuhkan di Era Digital - Tessa Lonika Simanullang; Pingky Monica Hasugian; Depi Yohana Manurung; Limra Nababan; Abdi Fristho Hutasoit; Jamaludin Jamaludin (Lembaga Pengembangan Kinerja Dosen, 2024)
The development of the era which is known as the digital era has provided changes and challenges for the world of education and also in the economic and other fields. The digital era is a more advanced development that will make everything digital in accordance with the preparation of more professional Civics teachers for the future in creating the skills and competencies needed in the digital era. Preparations must be made from now on, where every teacher learns how to use digital systems which must be adapted to learning needs in the digital era. The research method used is the library study method which is research carried out using library literature using a library study approach which is a supporting material for completing and obtaining research results about professional teachers for the future needed in the digital era. Teachers prepare themselves to create skills and competencies in the digital era.